Efficacy of “Attachment-Based Compassion Therapy” in the Treatment of Fibromyalgia: A Randomized Controlled Trial - Montero-Marín, Jesús; Navarro-Gil, Mayte; Puebla-Guedea, Marta; Luciano, Juan V.; Van Gordon, William; Shonin, Edo; García-Campayo, Javier (Frontiers in Psychiatry, 2018)
Objective: There is a growing interest in evaluating the effectiveness of compassion interventions for treating psychological disorders. The present study evaluated the effectiveness of ‘Attachment-Based Compassion Therapy’ (ABCT) in the treatment of fibromyalgia, and the role of psychological flexibility as a mediator of improvements. Methods: A total of 42 patients with fibromyalgia were randomly assigned to ABCT or relaxation (active control group). Both the intervention and control condition were combined with treatment as usual (TAU). The primary outcome was functional status (FIQ), and the secondary outcomes were clinical severity (CGI-S), pain catastrophizing (PCS), anxiety (HADS-A), depression (HADS-D), quality of life (EQ-5D), and psychological flexibility (AAQ-II). Differences between the groups were estimated using mixed-effects models, and mediation assessments were conducted using path analyses. Results: The ABCT group demonstrated superior outcomes compared to the relaxation group, including better FIQ values after treatment (B=-3.01; p=0.003). Differences in FIQ were maintained at 3-month follow-up (B=-3.33; p=0.001). The absolute risk reduction in ABCT compared to relaxation increased by 40.0%, with an NNT=3 based on criteria of ≥50% FIQ reduction after treatment. Psychological flexibility had a significant mediating effect on improvements. Conclusions: These results suggest that ABCT combined with TAU appears to be effective in the treatment of fibromyalgia symptoms.